Respuestas
Respuesta dada por:
1
Bien te plantean la ecuacion como ![x=x(x-1) x=x(x-1)](https://tex.z-dn.net/?f=x%3Dx%28x-1%29)
Entonces te piden que encuentres x para 3 y x para 2
Por lo tanto:
![x=3(3-1) x=3(3-1)](https://tex.z-dn.net/?f=x%3D3%283-1%29+)
![x=3(2)
x=3(2)](https://tex.z-dn.net/?f=x%3D3%282%29%0A)
![x=6 x=6](https://tex.z-dn.net/?f=x%3D6)
![x=2(2-1) x=2(2-1)](https://tex.z-dn.net/?f=x%3D2%282-1%29)
![x=2(1) x=2(1)](https://tex.z-dn.net/?f=x%3D2%281%29)
![x=2 x=2](https://tex.z-dn.net/?f=x%3D2)
Entonces te piden que encuentres x para 3 y x para 2
Por lo tanto:
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años